2013
DOI: 10.1590/s1807-55092013005000005
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre o índice de massa corporal e a coordenação motora em crianças

Abstract: ResumoO propósito do estudo foi analisar a associação entre o índice de massa corporal (IMC) e a coordenação motora (CM). Foram avaliadas 794 crianças (seis a nove anos) de ambos sexos na CM, com a bateria de testes KTK. O IMC foi calculado a partir das medidas de peso e estatura [Peso(kg)/Estatura (cm 2 )]. Quer nas meninas (χ 2 = 93,96; p < 0,001) quer nos meninos (χ 2 = 46,98; p < 0,001) ocorreram diferenças signifi cativas na CM entre os três grupos do IMC (normoponderais, sobrepeso, obesos). Os normoponde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
2
2
0
7
Order By: Relevance
“…In addition, it was found that BMI was inversely related to the KTK motor quotient values, except for shifting platforms motor quotient task. These results corroborate previous studies on the inverse relationship between adiposity indicators (BMI or BF%) and TMQ values of the KTK test 5,7,25,[27][28][29] . However, some of these investigations have shown weak to moderate correlation 7,[27][28] , while another study revealed high correlation 5 between these variables.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it was found that BMI was inversely related to the KTK motor quotient values, except for shifting platforms motor quotient task. These results corroborate previous studies on the inverse relationship between adiposity indicators (BMI or BF%) and TMQ values of the KTK test 5,7,25,[27][28][29] . However, some of these investigations have shown weak to moderate correlation 7,[27][28] , while another study revealed high correlation 5 between these variables.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding physical activity, as in this study, Morrison et al [25] reported that children with high body fat percentages and low levels of physical activity showed worse motor performance. Another study evaluated 794 children and concluded that low levels of physical activity were negatively associated with motor ability between the overweight/obese groups [26].…”
Section: Resultsmentioning
confidence: 99%
“…O fato de crianças com sobrepeso e obesidade apresentarem piores desempenhos em tarefas específicas pode ser justificado pela influência de hábitos sedentários nessas crianças e consequentemente reduzidos níveis de desempenho motor (Melo & Lopes, 2013).…”
Section: Discussionunclassified
“…Segundo Pelozin et al, (2010), o aumento dos níveis de obesidade na escola tem sido explicado pelos crescentes níveis de sedentarismo e inatividade física de crianças e adolescentes. O sedentarismo por sua vez, pode impactar negativamente na coordenação motora repercutindo no aumento do Índice de Massa Corporal (IMC) (Melo & Lopes, 2013).…”
Section: Introductionunclassified